Coronin 1A inhibits neurite outgrowth in PC12 cells - Terzi, Yunus Kasim; Kocaefe, Yusuf Cetin; Ayter, Sukriye (Neuroscience letters, 2014)
•Remodeling of actin cytoskeleton plays an important role in axonal sprouting.•Overexpression of Coronin 1A in PC12 cells effects neurite outgrowth.•Coronin 1A has an inhibitory effect on neurite outgrowth in vitro. Regenerative response to central nervous system damage in mammals is limited because of inhibitor signals which consist of myelin associated inhibitor proteins and chondroitin sulfate proteoglycans. Inhibitor signals mainly affect cytoskeleton elements which are important for axonal sprouting and neurite outgrowth. Coronin 1A is an actin cytoskeleton associated protein. Coronin 1A shows its effect on actin cytoskeleton through binding to the Arp2/3 complex which is a key nucleator of actin polymerization and regulates its activation on actin cytoskeleton. Coronin 1A–Arp2/3 interaction is regulated by phosphorylation of Coronin 1A from the C and N terminal region. Thus, Coronin 1A–Arp2/3 complex is one of the targets of inhibitory signaling cascades. The aim of this study was to investigate the effect of Coronin 1A on neurite outgrowth in PC12 cells in vitro. The results showed that Coronin 1A is expressed in differentiated PC12 cells and localized along axonal sprouting region of the neurites. Other results showed that overexpression of Coronin 1A in PC12 cells effects neurite outgrowth. Neurite lengths of the Coronin 1A overexpressing PC12 cells were lower than the untransfected (p<0.001) and control transfected (p=0.002) PC12 cells. These results indicate that Coronin 1A has an inhibitory effect on neurite outgrowth in vitro.